2019
DOI: 10.1371/journal.ppat.1007856
|View full text |Cite
|
Sign up to set email alerts
|

The ROP16III-dependent early immune response determines the subacute CNS immune response and type III Toxoplasma gondii survival

Abstract: Toxoplasma gondii is an intracellular parasite that persistently infects the CNS and that has genetically distinct strains which provoke different acute immune responses. How differences in the acute immune response affect the CNS immune response is unknown. To address this question, we used two persistent Toxoplasma strains (type II and type III) and examined the CNS immune response at 21 days post infection (dpi). Contrary to acute infection studies, type III-infected mice had higher numbers of total CNS T c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(65 citation statements)
references
References 75 publications
1
64
0
Order By: Relevance
“…Recent work has shown that all strains of T. gondii use the effector protein TgIST to block STAT1 signaling and thus inhibit IFN-γ–associated antimicrobial mechanisms after day 5 of infection (Gay et al, 2016; Olias et al, 2016). Interestingly, the ability to use the CEP strain shows that the loss of ROP16 results in a marked reduction in parasite levels as early as 4–5 dpi, which is even more significant by 10 dpi and has been extended to the chronic phase of infection (Tuladhar et al, 2019). Here, transcriptional profiling of macrophages infected and injected by CEP in vivo showed that suppression of IFN-γ–dependent innate immune mechanisms was only observed in infected cells, consistent with the role of TgIST as a late effector protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that all strains of T. gondii use the effector protein TgIST to block STAT1 signaling and thus inhibit IFN-γ–associated antimicrobial mechanisms after day 5 of infection (Gay et al, 2016; Olias et al, 2016). Interestingly, the ability to use the CEP strain shows that the loss of ROP16 results in a marked reduction in parasite levels as early as 4–5 dpi, which is even more significant by 10 dpi and has been extended to the chronic phase of infection (Tuladhar et al, 2019). Here, transcriptional profiling of macrophages infected and injected by CEP in vivo showed that suppression of IFN-γ–dependent innate immune mechanisms was only observed in infected cells, consistent with the role of TgIST as a late effector protein.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic Toxoplasma -Cre strains of T. gondii (Pru-Cre-tdTomato) were generated as previously described (Koshy et al, 2010). The engineering of the CEPΔROP16III strain is fully described in Tuladhar et al (2019). In brief, CEPΔhpt was cotransfected with four plasmids: two engineered with guide RNAs to upstream or downstream 21-mers for the rop16 locus, the pTKO plasmid engineered to contain 500-bp ROP16 homology regions surrounding the hypoxanthine phosphoribosyltransferase hxgprt cassette and a toxofilin-Cre cassette, and one plasmid containing the coding sequence for tdTomato under the GRA2 promoter.…”
Section: Methodsmentioning
confidence: 99%
“…5C, S3)-is intriguing. These data suggest that type II and type III strains may have different rates of conversion from tachyzoites to bradyzoites in vivo, with the type III strain trailing behind the type II strain at the D21 timepoint, despite the fact that type III strains are very capable of forming cysts in vivo 23,32,61 . We recently described how the host immune response at the same time point differs between these strains 32 , leading to a proverbial chicken-or-the-egg question.…”
Section: Especially Cd8 T Cells Hone-in On Tinsmentioning
confidence: 91%
“…Finally, to enable our ability to identify both universal and strainspecific neuron manipulations, we utilized mice infected with either of the canonical, persistent T. gondii strains. These strains-belonging to either the type II and type III lineages-are genetically distinct, express different polymorphs of some injected effector proteins 24,29,31,30,28,25,27 and are known to drive distinct CNS inflammatory responses 32 . Thus, with this combination of tools, we sought to define T. gondii's strain-specific and universal effects on neurons during an in vivo infection.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, very little is known about the neuron-T. gondii interaction, especially in vivo. What we do know about host cell-T. gondii interactions-that T. gondii secretes many effector proteins into host cells prior to and after full host cell invasion and that these effector proteins can be polymorphic between T. gondii strains, leading to strain-specific host cell manipulations-comes primarily from in vitro studies in fibroblasts and immune cells (3,(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%